Quality and Production of Forage - Tufarelli, Vincenzo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The book ""Quality and Production of Forage"" is intended to keep readers updatedon the developments occurring in this field. As it is apparent that livestockanimals are important throughout the world because of the meat, milk and eggthey produce, knowledge about the forages available to animals must also beconsidered for increased production, quality and efficiency. This book providesinformation that readers will find considerably invaluable about forage feeds, suchas grass, legumes, and straw. The book is composed of ten papers, focusing on awide range of research activities and topics that feature the following concepts offorage: the effect of conservation method on forage protein value; Microbial thecomposition and mycotoxin content in forage; genetic diversity of forages; timelysowing to maximize yield for both grain and biomass; ensiling treatments onforage quality; the qualitative characteristics of different accessions of new foragespecies; forage policy influencing feed costs; feeding forage on animal health;high-protein tropical forages as alternative sources for poultry; impact of foragesin poultry diet and significance of forages in sustainable poultry productionsystems. This book will be an invaluable reference for students and professionalsin agricultural science and grassland and animal husbandry researches.